Pengaruh Iklan di Media Sosial dan Platform Donasi Streamer Terhadap Peningkatan Aktivitas Judi Online Dihubungkan dengan Pasal 27 Ayat 2 Undang-Undang Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik - Saptaning Ruju Paminto; Ibrahim Khalil Ahmad; Zenal Syaepul Rohman; Neng Diana; Laela Sari; Ajmal Ghajwan (International Forum of Researchers and Lecturers, 2024)
The rapid development of technology and social media has led to an increase in online gambling activities, with promotional advertisements on social media and streamer donation platforms serving as one of the main contributing factors. This study aims to analyze the impact of these advertisements on the rise of online gambling activities, with a legal perspective based on Article 27 Paragraph 2 of Law Number 11 of 2008 concerning Information and Electronic Transactions. This research employs a descriptive-analytical approach through regulatory analysis and case studies. The results indicate that the presence of online gambling advertisements on digital platforms violates existing legal provisions and has potential social impacts.